Implementasi Program Electronic Kinerja (E-Kinerja) Aparatur Sipil Negara (ASN) DI Badan Kepegawaian Daerah Kabupaten Serdang Bedagai - Muhammad Farhan Rizki; Asima Yanti Sylviana Siahaan (SAJJANA: Public Administration Review, 2023)
The State Civil Service (ASN) E-Performance Program is a new State Civil Service (ASN) performance monitoring system that replaces the manual system which has shortcomings, such as the existence of State Civil Service (ASN) working not according to their duties, principals, and functions and not based on a merit system. The research method used is descriptive with a qualitative approach. The data obtained were then processed qualitatively with the theoretical approach of the policy implementation model of Donald Van Meter and Carl Van Horn. The results showed that the implementation of the State Civil Service (ASN) E-Performance Program at the Regional Personnel Agency of Serdang Bedagai Regency had been going well. However, the facilities and infrastructure of the The State Civil Service (ASN) E-Performance Program are not optimal because they are still experiencing problems, namely network constraints and they don’t have an ethical assembly.